Bioactive Chattels and Health Benefit Applications of Trametes versicolor - Mili, Shah; Rami, Nehal (Asian Journal of Biological and Life Sciences)
Mushrooms have as of now become an outstanding subject because of their diverse remedial properties. Of these, Trametes species have been exploited for epochs in traditional and conventional medication for the treatment of different kinds of ailments and sicknesses. Medicinal properties of Trametes versicolor are accentuated in several studies and are surveyed here as review article. The point of features of this review article is to sum up the accessible data on Trametes versicolor, including its bioactive components and their properties with different applications in medical advantages and current flow status of scientific exploration.
Keywords: Bioactive chemicals; Health; Mushroom; Trametes versicolor